2004
DOI: 10.1227/01.neu.0000137656.59536.0e
|View full text |Cite
|
Sign up to set email alerts
|

Operative Findings and Outcomes of Microvascular Decompression for Trigeminal Neuralgia in 35 Patients Affected by Multiple Sclerosis

Abstract: Results of MVD in trigeminal neuralgia MS patients are much less satisfactory than in the idiopathic group, indicating that central mechanisms play a major role in pain genesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 28 publications
1
58
0
3
Order By: Relevance
“…Recent literature favors multiple causes, including the possibility of both central MS lesions of the trigeminal pathway and peripheral vascular compression of the trigeminal REZ as causes that are not mutually exclusive. 4,[7][8][9] Initial studies examining the role of MVD for treatment of patients with both MS and TN have yielded mixed results. Resnick, et al, 20 examined five patients who had previously undergone unsuccessful percutaneous procedures, and reported better outcomes in two who had received MVD with partial rhizotomy compared with MVD alone.…”
Section: Resultsmentioning
confidence: 99%
“…Recent literature favors multiple causes, including the possibility of both central MS lesions of the trigeminal pathway and peripheral vascular compression of the trigeminal REZ as causes that are not mutually exclusive. 4,[7][8][9] Initial studies examining the role of MVD for treatment of patients with both MS and TN have yielded mixed results. Resnick, et al, 20 examined five patients who had previously undergone unsuccessful percutaneous procedures, and reported better outcomes in two who had received MVD with partial rhizotomy compared with MVD alone.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of MS, a plaque of demyelination encompasses the root entry zone of the trigeminal nerve in the pons [21]. Additionally, several studies have also described the association of a neurovascular conflict in a minority of patients [4,22,23,24]. Love and Coakham [20] demonstrated that demyelination is found to extend along the proximal part of the trigeminal nerve root and, in some cases, right up to its junction with the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Burchiel and Slavin [3 ]classified the MS-related TN as symptomatic. TN secondary to MS is additionally more often difficult to manage pharmacologically and surgically, with lower response rates than CTN [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…В тех случаях, ко-гда клиника классической НТН сопровождается чувствительным дефицитом, используют термин чувствительная тригеминальная нейропатия [331,423]. У больных рассеянным склерозом также наблюдается НТН, которую многие авторы относят ко вторичной НТН [63,74,154,158,169,170,184,340,354,365,366,378].…”
Section: от истоков к современному взгляду на патогенезunclassified